Neoclassical Growth Model with Overlapping Generations - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
notes on growth models with overlapping generations (OLG) structure
Keywords: A1; 330; growth models; OLG